Nghiên cứu đặc điểm đường đẳng nhiệt hấp phụ nitroglyxerin từ pha lỏng bằng một số loại than hoạt tính - Khuê, Đỗ Ngọc; Thiệp, Tô Văn; Hoàng, Nguyễn Văn; Minh, Đỗ Bình (Vietnam Journal of Chemistry, 2014)
The studied results showed that the adsorption of nitro glycerine (NG) by activated carbon from liquid phase do not perfectly accord to Langmuir and Freundlich theories. However, in the given space of concentration of NG can use Freundlich theory to explain adsorptive phenonmenons. The maximum capacity of the activated carbons (a∞) is about 140 - 270 mgr NG/gr